2019
DOI: 10.1186/s12913-019-4815-5
|View full text |Cite
|
Sign up to set email alerts
|

Access to specialty healthcare in urban versus rural US populations: a systematic literature review

Abstract: BackgroundAccess to healthcare is a poorly defined construct, with insufficient understanding of differences in facilitators and barriers between US urban versus rural specialty care. We summarize recent literature and expand upon a prior conceptual access framework, adapted here specifically to urban and rural specialty care.MethodsA systematic review was conducted of literature within the CINAHL, Medline, PubMed, PsycInfo, and ProQuest Social Sciences databases published between January 2013 and August 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 94 publications
4
127
3
2
Order By: Relevance
“… 10 Because a negative result has an extremely low risk of reaction (more than 90% negative predictive value), 19 pediatricians can safely recommend peanut introduction, thus reducing the need for allergy referrals and avoiding possible bottlenecks. 20 Previous research has indicated that both urban and rural areas face challenges in accessing specialty health care services, 21 therefore pediatricians who screen for peanut allergy could help provide an allergy assessment for more infants. If the sIgE test result is positive, an infant may or may not be allergic to peanut and should be referred to an allergist for further assessment.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Because a negative result has an extremely low risk of reaction (more than 90% negative predictive value), 19 pediatricians can safely recommend peanut introduction, thus reducing the need for allergy referrals and avoiding possible bottlenecks. 20 Previous research has indicated that both urban and rural areas face challenges in accessing specialty health care services, 21 therefore pediatricians who screen for peanut allergy could help provide an allergy assessment for more infants. If the sIgE test result is positive, an infant may or may not be allergic to peanut and should be referred to an allergist for further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Few healthcare personnel (0.5%), interviewed patients (1.7%), and surveyed patients (0.9%) reported culture or stigma-related care barriers or facilitators, and none reported language. The distributions of barriers across themes also differed significantly between our results from interviews, surveys, and a systematic review of the rural specialty literature (Cyr, Etchin, et al, 2019 TA B L E 3 (Continued) have inherent risks for personal bias, although our use of a team approach, interview scripts, and deviant cases (2 favourable, 2 poor outcomes) limit this possibility.…”
Section: Discussionmentioning
confidence: 70%
“…and (c) Does the distribution of these care access determinants vary from conceptual frameworks in the prior literature, and if so, how? (Cyr, Etchin, et al, 2019;Levesque et al, 2013).…”
Section: Aimsmentioning
confidence: 99%
“…Researchers note that access to healthcare is a poorly defined construct, with insufficient understanding of differences in facilitators and barriers between urban versus rural specialty care (Cyr, Etchin, Guthrie, & Benneyan, 2019). They say that long delays or complete inaccessibility to primary and specialty care are common across the United States (Kablan, OulaĂŻ, & Elliott, 2015;Steinman, Shoben, Dembe, & Kelleher, 2015).…”
Section: Research Questionsmentioning
confidence: 99%